Corrosion Prevention of Aluminium in 1 M HCl by Surface Deposition of Nickel Titanate - Beenakumari,K.S. (2013)
A different approach for protecting the aluminium in 1M HCl is done by strengthening the surface oxide film of aluminium with nickel titanate particles. Weight loss methods, open circuit potential measurements and polarization techniques are used to measure the corrosion behaviour of aluminium samples. The corrosion rate of nickel titanate deposited aluminium shows lower values compared to pure aluminium in HCl medium. The intermixing of aluminium oxide with nickel titanate enhances the corrosion resistance property of the aluminium oxide layer on the surface of aluminium and thereby reduces the coulombic and non-coulombic loss of metal.